Stillbirth due to SARS‐CoV‐2 placentitis without evidence of intrauterine transmission to fetus: association with maternal risk factors. (1st June 2022) - Konstantinidou, A. E.; Angelidou, S.; Havaki, S.; Paparizou, K.; Spanakis, N.; Chatzakis, C.; Sotiriadis, A.; Theodora, M.; Donoudis, C.; Daponte, A.; Skaltsounis, P.; Gorgoulis, V. G.; et al.
Abstract: Objectives: To describe the placental pathology, fetal autopsy findings and clinical characteristics of pregnancies that resulted in stillbirth owing to severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) placentitis, and to identify potential risk factors. Methods: This was a prospective multicenter study of non‐vaccinated pregnant women affected by coronavirus disease 2019 (COVID‐19) in Greece from April 2020 to August 2021. A total of 165 placentas were examined histologically and six cases of stillbirth associated with SARS‐CoV‐2 placentitis were retrieved. Complete fetal autopsy was performed in three of these cases. Gross, histopathological, immunohistochemical, molecular and electron microscopy examinations were carried out in the stillbirth placentas and fetal organs. The histological findings of cases with SARS‐CoV‐2 placentitis were compared with those in 159 cases with maternal COVID‐19 which resulted in a live birth. Regression analysis was used to identify predisposing risk factors for SARS‐CoV‐2 placentitis. Results: The placentas of all six stillborn cases showed severe and extensive histological changes typical of SARS‐CoV‐2 placentitis, characterized by a combination of marked intervillositis with a mixed inflammatory infiltrate and massive perivillous fibrinoid deposition with trophoblast damage, associated with intensely positive immunostaining for SARS‐CoV‐2 spike protein, the presence of virions on electron microscopy and positive reverse‐transcription polymerase chain reaction test of placental tissues. The histological lesions obliterated over 75% of the maternal intervillous space, accounting for intrauterine fetal death. Similar histological lesions affecting less than 25% of the placenta were observed in seven liveborn neonates, while the remaining 152 placentas of COVID‐19‐affected pregnancies with a live birth did not show these findings. Complete fetal autopsy showed evidence of an asphyctic mode of death without evidence of viral transmission to the fetus. The mothers had mild clinical symptoms or were asymptomatic, and the interval between maternal COVID‐19 diagnosis and fetal death ranged from 3 to 15 days. Statistically significant predisposing factors for SARS‐CoV‐2 placentitis included thrombophilia and prenatally diagnosed fetal growth restriction (FGR). Multiple sclerosis was seen in one case. Conclusions: SARS‐CoV‐2 placentitis occurred uncommonly in COVID‐19‐affected pregnancies of non‐vaccinated mothers and, when extensive, caused fetal demise, with no evidence of transplacental fetal infection. Thrombophilia and prenatally detected FGR emerged as independent predisposing factors for the potentially lethal SARS‐CoV‐2 placentitis. © 2022 International Society of Ultrasound in Obstetrics and Gynecology.